2008
DOI: 10.1371/journal.pone.0003907
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Genetic Loci Control Plasma HIV-RNA and Cellular HIV-DNA Levels in HIV-1 Infection: The ANRS Genome Wide Association 01 Study

Abstract: Previous studies of the HIV-1 disease have shown that HLA and Chemokine receptor genetic variants influence disease progression and early viral load. We performed a Genome Wide Association study in a cohort of 605 HIV-1-infected seroconverters for detection of novel genetic factors that influence plasma HIV-RNA and cellular HIV-DNA levels. Most of the SNPs strongly associated with HIV-RNA levels were localised in the 6p21 major histocompatibility complex (MHC) region and were in the vicinity of class I and III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
141
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 48 publications
11
141
1
2
Order By: Relevance
“…This idea has long been supported by both functional studies examining the response and quality of ES CD8 ϩ T cells (2, 3, 5, 10, 36-40) and genome-wide association studies identifying major histocompatibility complex class I alleles (such as HLA-B*57 and HLA-B*27) (41)(42)(43)(44)(45)(46). In addition, these protective HLA alleles have been shown to be overrepresented in multiple ES cohorts (5,41,(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 97%
“…This idea has long been supported by both functional studies examining the response and quality of ES CD8 ϩ T cells (2, 3, 5, 10, 36-40) and genome-wide association studies identifying major histocompatibility complex class I alleles (such as HLA-B*57 and HLA-B*27) (41)(42)(43)(44)(45)(46). In addition, these protective HLA alleles have been shown to be overrepresented in multiple ES cohorts (5,41,(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 97%
“…Genome-wide association studies (GWASs) have shown that variation in HLA class I region has the greatest differential influence on HIV viral load control (17)(18)(19)(20)(21)(22). Delineating the precise "causal" locus/loci, however, is problematic in the rich environment of functionally related, highly polymorphic, and tightly linked disease candidate loci located within the MHC.…”
Section: Significancementioning
confidence: 99%
“…In most studies, a quantitative measure of VL is used without reference to estimated date of infection (EDI), under the assumption that patients are seldom observed during acute-phase (peak) infection and that the early chronic-phase (set-point) VL is usually stable for years in patients with no apparent manifestations of immunodeficiency. Factors known or suspected to influence VL range from viral mutations (changes in replication fitness or switches in coreceptor tropism) (15,28,39,72) to host genes that govern innate and adaptive immune responses (54,75,81,83,84,86).Within the human nuclear genome, human leukocyte antigen (HLA) class I genes are the most convincing (and universally applicable) quantitative trait loci for HIV-1 viremia (14,16,17,66). However, the individual HLA alleles, haplotypes, and supertypes with reported impacts on HIV-1 VL are not always clear because their distribution and patterns of linkage disequilibrium often differ from one population to another (7,53,63).…”
mentioning
confidence: 99%